PENGARUH TINGKAT PENGETAHUAN DAN SIKAP PERAWAT TERHADAP PENERAPAN STANDAR PROSEDUR OPERASIONAL (SPO) PEMASANGAN INFUS DI RS PKU MUHAMMADIYAH BANTUL - Qurratul 'Aini; Muhammad Firdaus (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2014)
Most of action for infusion in the emergency department. Action of infusion more frequently performed by nurses and should be in accordance with standard operating procedures (SOP). The occurrence of plebitis incident, swollen, and trauma of due to repeated infusion is result of actions that do not prioritize of the patient safety. The purpose of research is knowing influence the level of knowledge and attitudes of nurses toward the implementation of Standard Operating Procedures in infusion. This research used descriptive quantitative research methods with cross sectional. The respondent of it is nurses working in the emergency department of PKU Muhammadiyah Hospital Bantul. Data was collected using a questionnaires and observation. The analytical tool used are univariate, bivariate, and multivariate. Results is the level of knowledge most of nurses in good category (80,00%), the attitude of most of the nurses has a good category (53,33%) and the application of standard operating procedures infusion majority of categories has been implemented (53,33%). There is a relationship between the level of knowledge and the application of standard operating procedures (p<0,05). There is a relationship between the attitude and the application of standard operating procedures (p<0,05). The magnitude of the influence level of knowledge and attitudes of nurses toward the implementation of SOP for 53,4% (R Square) while the remaining 46,6% is explained by other variables. Conclusion is there is influence between knowledge and attitude toward the implementation of standard operating procedures of infusion in RS PKU Muhammadiyah Bantul. The suggestion is the hospital should be providing the instrument of infusion accordance with the principles of safety and alertness in the application of standard operating procedures of infusion.